Needs Assesment of Adolescent Health Services - Khoiriyah Isni; Lina Handayani (International Journal of Public Health Science (IJPHS), 2017)
Health problems surround the adolescent rises everytime, yet it does unexcelled with their awareness or knowledge about that problems. The adolescent health service that are poorly accesced by the adolescent become the indicator that proves that the adolescent health services are not fully known and utilized yet. The assesment of adolesccent health services need has to be done so that it can be fully understand by the helper, target and stakeholder. This study aimed to analyse the adolescent health service need in Karang Bendo, Banguntapan, Bantul, Yogyakarta, Indonesia. The study was conducted in 2016 using cross-sectional approach. The results revealed that the level of adolsecent’s knowledge are still relatively poor: reproductive health knowledge (44.1%), HIV/AIDS (41.2%), smoke (50%), drugs (58.8%), and healthy lifestyle () (47.1%). The majority of respondents said that they need health services about reproduction health (94.1%), HIV/AIDS (91.2%), smoke (91.2%), drugs (88.2%) and healthy lifestyle (91.2%).